2022
DOI: 10.3390/diagnostics12061363
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Repetitive Cell-Free DNA in Cancer Liquid Biopsies

Abstract: Liquid biopsy is a broad term that refers to the testing of body fluids for biomarkers that correlate with a pathological condition. While a variety of body-fluid components (e.g., circulating tumor cells, extracellular vesicles, RNA, proteins, and metabolites) are studied as potential liquid biopsy biomarkers, cell-free DNA (cfDNA) has attracted the most attention in recent years. The total cfDNA population in a typical biospecimen represents an immensely rich source of biological and pathological information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 131 publications
1
13
0
Order By: Relevance
“…Extended testing validated this finding in patients with lung (NSCL, SCL), esophageal, ovarian, pancreatic, and liver cancers; other cancer types remain to be thoroughly analyzed. L1 desilencing was previously considered as a cancer biomarker detectable by hypomethylation in circulating cell-free DNA in liquid biopsies (Ardeljan et al, 2017;Gezer et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extended testing validated this finding in patients with lung (NSCL, SCL), esophageal, ovarian, pancreatic, and liver cancers; other cancer types remain to be thoroughly analyzed. L1 desilencing was previously considered as a cancer biomarker detectable by hypomethylation in circulating cell-free DNA in liquid biopsies (Ardeljan et al, 2017;Gezer et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Extended testing validated this finding in patients with lung (NSCL, SCL), esophageal, ovarian, pancreatic, and liver cancers; other cancer types remain to be thoroughly analyzed. L1 desilencing was previously considered as a cancer biomarker detectable by hypomethylation in circulating cell-free DNA in liquid biopsies (Ardeljan et al, 2017; Gezer et al, 2022). Here, we demonstrate that the epigenetic dysregulation of L1 can generate an additional type of biomarker – circulating autoantibodies against L1 antigens – that can be detected by a simple and robust blood test.…”
Section: Discussionmentioning
confidence: 99%
“…Significant research efforts in the last decade uncovered a rich landscape of cfDNA physico-chemical features (reviewed in [ 130 , 137 , 138 , 139 , 140 ]). Beyond hotspot mutations, numerous cfDNA features are candidate biomarkers, including (i) various genetic features, such as DNA sequence features ( Figure 4 A), chromosomal abnormalities ( Figure 4 B), and topological forms ( Figure 4 C); (ii) primary epigenetic markers such as DNA methylation ( Figure 4 D) and histone modifications ( Figure 4 E); and (iii) various secondary epigenetic features that cfDNA molecules attain intracellularly or extracellularly following disruption of the primary structure of DNA, such as binding to proteins, extracellular vesicles, or cell membranes ( Figure 4 F), and fragmentomic features ( Figure 4 G).…”
Section: Beyond Cfdna Hotspot Mutation Analysismentioning
confidence: 99%
“…It is not yet clear how cfDNA fragments are integrated into host genomes, but some evidence suggests that it may occur through the non-homologous end-joining (NHEJ) double-strand DNA-repair pathway [ 113 , 364 , 377 ]. Alternatively, ctDNA enriched in specific retrotransposons (e.g., a hot LINE-1 element) [ 139 , 378 , 379 ] could, by virtue of their inherent mobility, penetrate recipient cells and initiate tumor formation upon “cut-and-paste” insertion into host tumor suppressor genes [ 380 , 381 ]. While there is no direct evidence, it is interesting to speculate here on the possibility of lateral transfer of therapy resistance mutations from resistant cells to surrounding cells.…”
Section: Potential Pathological Effects and Biological Functions Of C...mentioning
confidence: 99%
“…Furthermore, the detection of circulating nucleic acids—comprised of segments of genomic DNA and various RNA types, such mRNA and noncoding RNAs—in serum or plasma is increasingly regarded as a potential biomarker in oncology [ 12 ]. Although many types of nucleic acids are present in bodily fluids, cell-free DNA (cfDNA) has to date received the most research attention and has demonstrated significant potential as a highly sensitive and specific biomarker for the management of numerous cancer types across all disease stages and phases of cancer management [ 13 ]. Although cfDNA is present in many types of bodily fluids, such as serum, plasma, urine, pleural fluid, cerebrospinal fluid, and saliva [ 14 , 15 , 16 , 17 ], blood (plasma and serum) represents the most extensively characterized source of cfDNA.…”
Section: Introductionmentioning
confidence: 99%